PEMANFAATAN LIMBAH PELEPAH PISANG SEBAGAI MEMBRAN SELULOSA RAMAH LINGKUNGAN UNTUK ADSORPSI PB (II): STUDI OPTIMASI - Rohmatun Nafi'ah; Muslikah Muslikah; Endra Pujiastuti (2026)
Banana sheath waste contains a high cellulose content and has potential to be utilized as an environmentally friendly adsorbent for heavy metal wastewater treatment. This study aimed to investigate the effect of pH variation and contact time on the adsorption capacity of Pb(II) ions using polyethylene glycol (PEG) 8%-modified banana sheath cellulose membrane. Cellulose was extracted from banana sheath (Musa paradisiaca) through alkaline treatment and bleaching processes, followed by the synthesis of cellulose acetate membrane using the phase inversion method with the addition of 8% PEG. Membrane characterization was carried out using Fourier Transform Infrared Spectroscopy (FTIR), while Pb(II) concentration analysis was performed using Atomic Absorption Spectroscopy (AAS). Adsorption experiments were conducted at pH variations of 4, 5, and 8 and contact times of 5, 10, and 15 min. FTIR analysis confirmed the presence of characteristic cellulose functional groups, including O–H, C–O, and C–O–C, indicating the successful incorporation of PEG into the membrane matrix. The adsorption results showed that the optimum condition was achieved at pH 8 with an adsorption capacity of 4.992 mg/g, while the optimum contact time was obtained at 15 min with an adsorption capacity of 4.890 mg/g. The increased adsorption capacity under alkaline conditions was attributed to the reduced competition between H? ions and Pb(II) ions for binding to the active sites of the adsorbent. Based on these findings, PEG-modified banana sheath cellulose membrane demonstrates promising potential as an environmentally friendly and low-cost alternative adsorbent for Pb(II) heavy metal removal.